Wood preservation in Malaysia / Normurni Ramli - Ramli, Normurni (2007)
Wood is treated to prevent it's from destroying agent. Wood preservative is the suitable process used to increase its service life to protect the timber structure. Wood preservative must be done and conscience so that the wood quality is guarantee and safe. So, wood preservative is the best technique for make sure the wood is free from the organism destroyer attack.